Costumers’ Preference at Armor Kopi Leuit - Siagian, Debora Requel Emeralda; Suminartika, Eti (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
Coffee shops are currently in great demand; thus the numbers of coffee shops show an increase, including in Bandung city. However, the number of customers at Armor Kopi Leuit Coffee Shop has decreased in number. The purposes of this study were to analyze costumers’ preferences for coffee and customers’ preferences for Armor Kopi Leuit coffee shop. The research method used was quantitative descriptive method, while the analytical instrument used was conjoint analysis. Samples were taken by convenience sampling and 100 samples were obtained. The results showed that coffee attributes that is considered the most important by consumers are tastes with strong coffee preferences, while consumer preferences for coffee shops included shop designs that provided closed and open spaces, easily accessible coffee shop locations, barista communication skills in explaining products, and a natural coffee shop atmosphere.